Patient Outcomes after Reirradiation of Small Skull Base Tumors using Stereotactic Body Radiotherapy, Intensity Modulated Radiotherapy, or Proton Therapy - Ng, Sweet Ping; Wang, He; Pollard, Courtney, III; Nguyen, Theresa; Bahig, Houda; Fuller, Clifton D.; Gunn, G. Brandon; Garden, Adam S.; Reddy, Jay P.; Morrison, William H.; Shah, Shalin; Rosenthal, David I.; Frank, Steven J.; Guha-Thakurta, Nandita; Ferrarotto, Renata; Hanna, Ehab Y.; Su, Shirley Y.; Phan, Jack (Journal of Neurological Surgery Part B: Skull Base, 2019)
Purpose The aim of this study was to evaluate outcomes of patients who received reirradiation for small skull base tumors utilizing either intensity modulated radiotherapy (IMRT), stereotactic body radiotherapy (SBRT), and proton radiotherapy (PRT).Methods Patients who received IMRT, SBRT or PRT reirradiation for recurrent or new small skull base tumors (< 60 cc) between April 2000 and July 2016 were identified. Those with < 3 months follow-up were excluded. Clinical outcomes and treatment toxicity were assessed. The Kaplan–Meier method was used to estimate the local control (LC), regional control (RC), distant control (DC), progression free survival (PFS), and overall survival (OS).Results Of the 75 patients eligible, 30 (40%) received SBRT, 30 (40%) received IMRT, and 15 (20%) received PRT. The median retreatment volume was 28 cc. The median reirradiation dose was 66 Gy in 33 fractions for IMRT/PRT, and 45 Gy in 5 fractions for SBRT. The median time to reirradiation was 41 months. With a median follow-up of 24 months, the LC, RC, DC, PFS, and OS rates were 84%, 79%, 82%, 60%, and 87% at 1 year, and 75%, 72%, 80%, 49%, and 74% at 2 years. There was no difference in OS between radiation modalities. The 1- and 2-year late Grade 3 toxicity rates were 3% and 11% respectively..Conclusions Reirradiation of small skull base tumors utilizing IMRT, PRT, or SBRT provided good local tumor control and low rates of Grade 3 late toxicity. A prospective clinical trial is needed to guide selection of radiation treatment modalities.
Keywords: Reirradiation; skull base; proton; stereotactic; IMRT